Quantum spacetime : mimicry of paths and black holes - Spaans, Marco, 1969- (Classical and quantum mechanics series., 2015)
Since its inception, general relativity has been unreceptive to a marriage with the quantum aspects of our universe. Following the ideas of Einstein, one may pursue an approach that allows spacetime itself to take centre stage. The quantum properties of matter are then carried by the dynamics of spacetime shape and connectivity. This monograph introduces the reader to the foundations of quantum spacetime in a manner accessible to researchers and students. Likewise, interested laymen that lack a strong background in quantum mechanics or spacetime studies but are keen to learn would find this in.